THE INFLUENCE OF WORK CULTURE, WORK ETHICS AND WORK ENVIRONMENT ON JOB SATISFACTION OF PT. INTERNUSA MANDIRI SURABAYA - Handoko, Nanang; Setiadi, Pompong Budi; Rahayu, Sri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Abstract Employee job satisfaction can be influenced by career paths, work environment, salary, company management, work ethics, work culture, social aspects of work and communication. There are many factors that affect employee job satisfaction, so this study takes three factors to serve as variables in the study, namely work culture, work ethics and work environment. The aims of this study was to determine the effect of work culture, work ethics and work environment partially and simultaneously on employee job satisfaction. The method used in this research is descriptive quantitative with a sample of 100 people. Based on the results of the study indicate that the three independent variables used have a partial and simultaneous effect on employee job satisfaction. This is evidenced by the value of T-Count > T-Table and F-Count > F Table. Thus it can be concluded that companies must continue to pay attention to and develop work culture and work environment in order to create a comfortable atmosphere and work ethic so that employees feel not burdened at work. Keywords: Job Satisfaction, Work Culture, Work Ethics. Work Environment